PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP PARTISIPASI ANGGOTA PADA KOPERASI BINA SEJAHTERA KELURAHAN TANGKERANG SELATAN PEKANBARU - Riris Lawitta Riris Lawitta; Rina Selva Johan Selva Johan; Hendripides Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Cooperative has expressly designated by the government as the container economy of the people. Government policy is in accordance with the 1945 Constitution article 33, paragraph 1. The development and growth of a cooperative is highly dependent on the quality and participation of its members. So that the success of the cooperative to be realized, the participation of members should be increased. There are several ways to increase the participation, that is material and non-material. With outstanding service quality will encourage the participation of members in participating in cooperative activities. This is due to benefit members and the results obtained when joining a cooperative member. This study aims to determine whether the dimensions of service quality has a significant impact on the participation of members of Koperasi Bina Sejahtera Pekanbaru. The method used is quantitative, data needed by researchers is a questionnaire and other documents that support of research undertaken. From the research that has been done, the regression equation Y = -3.818 + 0,588X1 + 0,355X2 + 0,334X3 + 0,118X4 + 0,134X5. Simultaneously the service quality affects participation (F-test of 9.113 with sig. 0.000 <0.05) and partially (t test) dimension of empathy and physical evidence did not affect participation. Testing the coefficient of determination shows the quality of services affects the participation of 43.5% (adjusted R-square = 0.435).Keywords: Foreign Ownership, Government Ownership and Agency Costs